Structural analysis of recombinant human ubiquitin-conjugating enzyme UbcH5c - Fangshu Wu; Junsheng Zhu; Honglin Li; Lili Zhu (Elsevier, 2017)
UbcH5c belongs to the ubiquitin-conjugating enzyme family and plays an important role in catalyzing ubiquitination during TNF-α--triggered NF-κB activation. Therefore, UbcH5c is a potent therapeutic target for the treatment of inflammatory and autoimmune diseases induced by aberrant activation of NF-κB. In this study, we established a stable expression system for recombinant UbcH5c and solved the crystal structure of UbcH5c belonging to space group P22121 with one molecule in the asymmetric unit. This study provides the basis for further study of UbcH5c including the design of UbcH5c inhibitors.